A case series of lacosamide as adjunctive therapy in refractory sleep‐related hypermotor epilepsy (previously nocturnal frontal lobe epilepsy). (25th February 2018) - Samarasekera, Shanika R.; Berkovic, Samuel F.; Scheffer, Ingrid E.
Summary: The aim of this study was to evaluate the efficacy and tolerability of open‐label lacosamide in patients with refractory sleep‐related hypermotor epilepsy. The study was a case review of eight patients with refractory sleep‐related hypermotor epilepsy treated with lacosamide. Seizure diaries compared the mean baseline seizure frequency with the most recent 3 months of follow‐up. Five (62.5%) patients were responders, defined as ≥50% reduction in seizure frequency, over a mean duration of exposure of 21.5 months. The mean maintenance dose of lacosamide was 400 mg/day. No‐one reported worsening of seizures. Lacosamide was well tolerated with initial fatigue being the main side‐effect. Lacosamide is a potentially efficacious adjunctive therapy in patients with refractory sleep‐related hypermotor epilepsy. A double‐blind placebo‐controlled study would determine its efficacy.